The power of positive thinking (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Optimism is clearly associated with better psychological health, as seen through lower levels of depressed mood, anxiety, and general distress. Most researchers at this point would also agree that optimism is connected to positive physical health outcomes, including decreases in the likelihood of re-hospitalization following surgery, the risk of developing heart disease, and mortality. In this track, we aim to provide a better understanding of positive thinking, and we offer multiple key actionable techniques to train yourself to think more optimistically. Learning Objectives Learn what dispositional optimism is, and how it benefits both our physical and mental health Learn classic cognitive distortions linked to thinking negatively, and how to identify and avoid them.